2015
DOI: 10.1200/jop.2014.001487
|View full text |Cite
|
Sign up to set email alerts
|

Validation of a Simple Screening Tool for Identifying Unmet Palliative Care Needs in Patients With Cancer

Abstract: The tool seems to be a valid method for identifying patients with cancer with complex PC needs who would benefit from a PC consult. Reliability testing, external validation, and demonstration of the utility of the tool as a decision aid all await confirmation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
60
0
6

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 63 publications
(69 citation statements)
references
References 15 publications
3
60
0
6
Order By: Relevance
“…One recent study estimated that 13.8 percent of intensive care unit admissions met criteria for palliative care consultation, 23 and a study in a large cancer center estimated that one-third of hospitalized cancer patients should receive a palliative care consultation. 24 In addition, we found that one-third of palliative care programs did not have recommended coverage-personnel available on site during weekday business hours and by telephone at all times. SOURCE Authors' analysis of data from the 2012-13 annual surveys of the National Palliative Care Registry.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…One recent study estimated that 13.8 percent of intensive care unit admissions met criteria for palliative care consultation, 23 and a study in a large cancer center estimated that one-third of hospitalized cancer patients should receive a palliative care consultation. 24 In addition, we found that one-third of palliative care programs did not have recommended coverage-personnel available on site during weekday business hours and by telephone at all times. SOURCE Authors' analysis of data from the 2012-13 annual surveys of the National Palliative Care Registry.…”
Section: Discussionmentioning
confidence: 96%
“…These can be administered by multiple types of hospital personnel, streamline the referral process, and reduce the odds that patients' needs are missed. 23,24,34 Managers should ensure that their palliative care programs collaborate with other related hospital programs such as advance care planning, case management, and pain services.…”
Section: Discussionmentioning
confidence: 99%
“…Palliative care need assessed by external screening using the "Palliative Care Screening Tool for heart failure patients" was scored with 6.8 out of a maximum of 12 points. Using the cut-off value of >5 of the original version of the "Five Item Palliative Care Screening Tool" by Glare et al validated in cancer patients as indicator for palliative care need [27,33], almost 80% of patients would have needed palliative care. Interestingly, the treating cardiologists recognized objective parameters for palliative care needs, like symptom burden, distress or decision-making quite frequently.…”
Section: Discussionmentioning
confidence: 99%
“…Screening for palliative care need: A modified version of the "FiveItem Palliative Care Screening Tool" developed by Glare et al was used to screen for potential palliative care need by the treating cardiologists [27,33]. The "Five-Item Palliative Care Screening Tool" was developed to screen advanced cancer patients for their potential palliative care need.…”
Section: Measurementsmentioning
confidence: 99%
See 1 more Smart Citation